2000
DOI: 10.5507/bp.2000.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Copper Level in the Blood Serum of Male Stutterers and the Occurrence of the Vibratio Brevis Phenomenon

Abstract: The blood serum copper level and the phonation start were investigated in sixteen male subjects with developmental stuttering (mean age = 25.8 years). A statistically significant decrease in blood serum copper level was revealed in the stutterers under study. The differences between their mode and mean values and that of the control group were 4.6 µmol/l and 3.1 µmol/l, respectively. The negative linear regression between the copper level in serum and the vibratio brevis phenomenon was registered in the stutte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…The result from Pesak and Opavsky [11] of low serum Cu in stuttering men was supported by a pilot study of stuttering men in our laboratory, without a control group (n = 23, plasma Cu = 14 mol/l vs. 14.1 mol/l Cu in the study by Pesak and Alm Opavsky [11] ). The pilot study also indicated a low level of Cp and a high level of estimated free Cu.…”
supporting
confidence: 49%
See 4 more Smart Citations
“…The result from Pesak and Opavsky [11] of low serum Cu in stuttering men was supported by a pilot study of stuttering men in our laboratory, without a control group (n = 23, plasma Cu = 14 mol/l vs. 14.1 mol/l Cu in the study by Pesak and Alm Opavsky [11] ). The pilot study also indicated a low level of Cp and a high level of estimated free Cu.…”
supporting
confidence: 49%
“…Alpha was set at 0.05 for all statistical tests. One-tailed tests were used for plasma Cu and Cp, based on the result of Pesak and Opavsky [11] . A two-tailed test was used for estimated free Cu.…”
Section: Statisticsmentioning
confidence: 99%
See 3 more Smart Citations